A Study on the Carbon Footprint of a Philippine Higher Education Institution using Streamlined Life Cycle Assessment - Jesuniño Aquino; Samantha Claire Bedia; Maria Caryll Ruiz; Alessandra Mikaela Zornosa (Chemical Engineering Transactions)
Higher education institutions (HEIs) have a key role in fostering sustainable development as academic organizations dedicated to research, education, and community service. As emissions rise, understanding and reducing major sources have become imperative. This study quantifies the carbon footprint of Mapúa Malayan Colleges Laguna (MMCL) for 2022 using a streamlined life cycle assessment methodology, which is a systematic framework that evaluates the environmental impacts throughout a product’s life cycle. This study aims to determine the total carbon footprint of MMCL for 2022, considering scopes that cover both indirect and direct emissions, with the objective of providing insights into HEI emissions and serving as a basis for sustainable mitigation and emission reduction efforts. Results show that the carbon footprint of MMCL in 2022 was 614,553 kg CO2-eq, with Scope 2 (electricity consumption) contributing the most emissions at 98.49 %, followed by Scope 1 (fuel consumption) at 1.16 %, and Scope 3 (solid waste) at 0.34 %.